Recent progress in analyses of GATA1 in hematopoietic disorders: a mini-review - Shimizu, Ritsuko; Yamamoto, Masayuki (Frontiers in Hematology, 2023)
GATA1 is an essential master regulator of erythropoiesis and megakaryopoiesis. Accumulating lines of evidence have shown that dynamic changes in GATA1 gene expression levels during erythropoiesis are crucial for proper erythroid differentiation. Since GATA1 is an X-chromosome gene, GATA1 knockout leads to embryonic lethal dyserythropoiesis in male mice, while heterozygous female mice can survive. In the past decade, it has become clear that germline GATA1 gene mutations leading to structural changes in the GATA1 protein are involved in congenital dyserythropoiesis in males. In contrast, decreased GATA1 expression levels, which cause embryonic lethal dyserythropoiesis in male mice, increase the risk of erythroleukemia development in female mice, while female GATA1-knockout mice do not show substantial phenotypic alterations in erythroid or megakaryocyte lineages. In this review, we summarize the recent progress in elucidating the roles of GATA1 in normal and pathogenetic erythropoiesis and discuss the possible mechanisms of pathogenesis of dyserythropoiesis and erythroleukemia.